What strategic studies are and are not: about a manifesto by Isabelle Duyvesteyn and James Worral - Fernandes, António Horta (2021)
The present paper intends to make a synthetic update of the "being" of strategy, evoking strategic studies, namely in the aspects concerning the object of strategy and the relationship between strategy and politics. This update is done by confronting it with a recent manifesto, by Isabelle Duyvestein and James Worral, important for its repercussions on the science of international relations, which suffers from many weaknesses and no less aporias. It is important, therefore, to deconstruct some of its assumptions, which have also been those uncritically accepted when International Relations touches on the problematic inherent to strategic studies or focuses on war.